Meloidogyne exigua attacking coffee trees in the state of Ceará Brazil - Ponte, J. Júlio da; Sena-Silva, Maria do Socorro (Pesquisa Agropecuaria Brasileira, 2014)
Meloidogyne exigua Goeldi, 1887, successively recorded in the Brazilian States of Rio de Janeiro, São Paulo, Minas Gerais, Paraná and Espírito Santo, has now been observed in the State of Ceará - in the mountains of Baturité and Ibiapaba - where this species of root-knot nematode is attacking roots of cofee trees, Coffee arabica L. An interesting morphological detail was observed among the specimens collected in the Ibiapada zone: the adult females are usually large, with lengths of 500-700 µ, as compared with the standard length of 450 µ.